The Legal System for the Conversion of Commercial Companies in the Light of the Rules of the Saudi Corporate System - Alomari, Mohammad S. (Bright Institute, 2022)
As Saudi Arabia gears towards economic advancement and openness, in line with its vision 2030, there is need to have a suitable business environment that is favorable for commercial companies to thrive and create more job opportunities for the population. One way to achieve this, is by ensuring that there is a proper legal framework that allows for the conversion of commercial companies from one form to another, which suits the country’s economic ambitions. This thus enables commercial companies to convert into legal structures that can adapt in the changing environment and ensure that they contribute greatly to Saudi Arabia’s economy. Commercial companies that may have initially been operating via forms that rendered them ineffective, can convert into forms that allows them to operate efficiently and ensure that they have a strong and competitive position in the market while not necessarily changing their legal structures. This research paper thus examines and critically analyses the legal framework in Saudi Arabia that governs the conversion of commercial companies as enshrined under the Saudi Arabia Company Law. This research paper aims to establish that a suitable legal system for the conversion of commercial companies in Saudi Arabia is crucial for the economic growth of the country.